Consumer Protection Agency Resolution No. 4/1 of the year 2022 Concerning The Life Span Of Goods = جهاز حماية المستهلك قرار رقم 1/4 لسنة 2022 بشأن العمر الافتراضى للسلع - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic